TWENTIETH CENTURY CANADIAN SCEINCE FICTION: AN ANALYTICAL NOTE ON CERTAIN DOMINANT THEMES - Jacob George (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
Modern science fiction being overwhelmingly an American phenomenon, a distinctive Canadian model or tradition that could be contrasted with the American one emerged only during the last couple of decades. The delayed flowering of science fiction and fantasy in the Canadian literary context is often attributed to a certain atrophy of the fantastic imagination in Canada. Yet, the rare appearance of science fictional flights' in pre-Second World War Canlit is best ascribed not to the aridity of the fantastic imagination, but to the fact that the preponderance of works that constitute the 'canon' of Canadian fiction are realistic or naturalistic. Such a marginalization of the fantastic mode appears to be the direct consequence of holding realistic and naturalistic paradigms as effective tools of nationalis